Trophoblast Development in the Murine Preimplantation Embryo - Underhill, Lori A.; Robins, Jared C. (Seminars in Reproductive Medicine, 2016)
Trophoblast cells of the murine placenta are derived from the trophectoderm (TE) cells of the preimplantation embryo. Establishment of the TE cell lineage is the result of a cell segregation event early in blastomere division. Models of cell lineage segregation suggest it is driven by the internalization of spatial information which induce or inhibit specific signaling pathways. Once segregated, TE cells undergo a differentiation event, resulting in both proliferative and terminally differentiated trophoblast cells. Thus, the development of a healthy, functional placenta relies on the well-choreographed events of trophoblast segregation, proliferation and differentiation. The pre and peri-implantation events that contribute to the development of the four main types of placental trophoblasts are the subject of this review. Identifying the components and promotors of trophoblast development will lead to a more comprehensive understanding of diseases associated with abnormal placentation and recurrent pregnancy loss.
Keywords: trophoblast; preimplantation; differentiation; segregation